Thyroid hormones and minerals in immunocorrection of disorders in autoimmune thyroid diseases - Kravchenko, Viktor; Zakharchenko, Tamara (Frontiers in Endocrinology, 2023)
Resume. Thyroid hormones and essential elements iodine (I), selenium (Se), iron (Fe), copper (Cu), zinc (Zn), calcium (Ca), magnesium (Mg), etc. play an important role in the work of many organs and systems of the body, including the immune system and the thyroid gland, and a violation of their supply can be the cause of pathological changes in them. In pathology, the interaction between thyroid hormones (TG), minerals and the immune system is disturbed. The review of the literature examines the immunomodulatory role of TG, minerals, their properties, and their participation in the pathogenesis of autoimmune thyroid diseases (AITD). The study of the relationship between the excess or deficiency of minerals and AITD is described. The basis of the development of AITD -Hashimoto's thyroiditis (HT), Graves' disease (GD), Graves' ophthalmopathy (GO) is the loss of immune tolerance to thyroid antigens -thyroid peroxidase (TPO), thyroglobulin (Tg) and thyroid-stimulating hormone receptor (TSH-R). Immune-mediated mechanisms -production of autoantibodies to thyroid antigens and lymphocytic thyroid infiltration -are involved in the pathogenesis of AITD. Insufficiency of regulatory T cells (Treg) and regulatory B cells (Breg), imbalance between Th17-lymphocytes and Treg-lymphocytes, abnormal production of pro-inflammatory cytokines has a significant influence on the progression of AITD. With AITD, the balance between oxidants and antioxidants is disturbed and oxidative stress (OS) occurs. The lack of modern effective pharmacological therapy of AITD prompted us to consider the mechanisms of influence, possibilities of immunocorrection of pathogenetic factors using TG, micro/macronutrients. In order to develop a more effective treatment strategy, as well as approaches to prevention, a critical analysis of the ways of immunotherapeutic use of dietary supplements of I, Se, Zn, Mg and other minerals in AITD was carried out.